2007
DOI: 10.1016/j.virusres.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the gene start sequences of pneumonia virus of mice

Abstract: The transcriptional start sequence of pneumonia virus of mice is more variable than that of the other pneumoviruses, with five different nine-base gene start (GS) sequences found in the PVM genome. The sequence requirements of the PVM gene start signal, and the efficiency of transcriptional initiation of the different virus genes, was investigated using a reverse genetics approach with a minigenome construct containing two reporter genes. A series of GS mutants were created, where each of the nine bases of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Two groups have reported success at generating a replicating form of recombinant PVM using a reverse genetics approach [19][20][21]. Using this system, Easton and colleagues [19,20] have explored the roles of the virus M2-1, M2-2, and P open reading frames of PVM strain 15 (Warwick) in supporting reporter gene activity in vitro and have evaluated the plasticity of the transcriptional start sites.…”
Section: Recombinant Pvmmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups have reported success at generating a replicating form of recombinant PVM using a reverse genetics approach [19][20][21]. Using this system, Easton and colleagues [19,20] have explored the roles of the virus M2-1, M2-2, and P open reading frames of PVM strain 15 (Warwick) in supporting reporter gene activity in vitro and have evaluated the plasticity of the transcriptional start sites.…”
Section: Recombinant Pvmmentioning
confidence: 99%
“…Using this system, Easton and colleagues [19,20] have explored the roles of the virus M2-1, M2-2, and P open reading frames of PVM strain 15 (Warwick) in supporting reporter gene activity in vitro and have evaluated the plasticity of the transcriptional start sites. Buchholz and colleagues [21] determined that the full G (attachment) protein was crucial for replication of PVM strain 15 (ATCC) in vivo while the G protein cytoplasmic tail alone promoted weight loss.…”
Section: Recombinant Pvmmentioning
confidence: 99%
“…NC_006579 bp 1 to 42), the PVM N gene start (bp 1036 to 1044 [32]), the PVM N noncoding region (bp 1045 to 1066) with flanking NotI and BamHI sites, the PVM trailer (PVM L noncoding region, GenBank accession no. NC_006579 bp 14653 to 14657), the PVM L gene end (bp 14781 to 14794 [32]), and the PVM 3= UTR (bp 14795 to 14885) with flanking XhoI and HindIII sites were inserted to replace the RSV sequences. All DNA fragments were synthesized by GeneArt (Invitrogen); sequences were confirmed prior to transfer in order to generate pGEM-PVM-Luc.…”
Section: Methodsmentioning
confidence: 99%
“…The MPV M2 gene had been suggested to be 875 nt long [33], whereas Renshaw et al [14] reported a 926-nt M2 sequence for CnPnVs based on the presence of the GS sequence upstream the location previously detected for MPV [34]. Consequently, the M2 gene length was re-determined as 928 and 921 nt for MPV isolates 15 and J3666, respectively.…”
Section: Full-genomic Characterisation Of the Italian Cnpnv Prototypementioning
confidence: 99%